Presentation: Language, nation, and Andean World - Godenzzi, Juan Carlos (1987)
Language, a creative activity, opens us to the unknown and makes possible a diagonal relationship with the other. Language defines something essential of the human being; it is his "daily fire", to say it with an image of Octavio Paz. Language is, at the same time, a human faculty and cultural knowledge; For this reason, it requires socially constituted signs and mechanisms, tributaries of a historical tradition. The plurality of aspects of language justifies the multiple treatments that we can make of it. The extraordinary success of linguistics in recent decades was fundamentally due to advances in the rigorous description of the structures and procedures of languages ​​taken as autonomous systems.